The Relationship Between Work Environment, Work Motivation, Work Discipline, and Employee Performance in the Safety Risk Quality Control Unit - Roro Maya Rizkita Sabrina (Innovation Business Management and Accounting Journal, 2024)
An organization's actions are primarily driven by its human resources, which also determine the rate of growth or decline of an organization. The ability of a company or organization to obtain quality work results and the desired quantity is greatly influenced by several factors, including work motivation, work discipline, and work environment. Motivational factors influence performance because motivational factors are a condition that moves humans towards a specific goal. Meanwhile, the discipline factor is a person's awareness and willingness to obey allapplicable company regulations and social norms. The next factor that influences employee performance is the work environment factor. This is because the work environment is a total of elements both within and outside the organization's boundaries that directly or indirectly impact managerial activities to achieve organizational goals. This research was conducted in the work environment at PT. Angkasa Pura II, especially at Soekarno-Hatta Cengkareng Airport, maximizes the best service, namely by providing a variety of modern airport support services supported by high-tech facilities, which is the airport's commitment to creating comfort for service users while in the airport environment. Airport-related services aim to support the creation of security, safety, and comfort for airport service users while in the airport area.